Analisis Faktor-Faktor Yang Mempengaruhi Minat Nasabah Menggunakan Produk Tabungan Umum Syariah Di BMT-UGT Nusantara Capem Jember Kota - Nuvailah Rosiyah; Nova Lupita Nur Wulandari; Dewi Elok Faiqoh; Nur Hidayat (Jurnal Ekonomi dan Bisnis Digital, 2025)
Baitul Maal Wat Tamwil (BMT) is a non-banking financial institution that supports community quality by supporting micro-enterprises by collecting funds from the community. The BMT UGT Sidogiri Cooperative began operating on June 6, 2000, and was converted to BMT UGT Nusantara in December 2020. This study aims to identify factors that influence customer interest in BMT UGT Nusantara's general savings products. The three main factors found are (1) clear and easy-to-understand product factors to inspire customer interest. (2) Service Factors: Friendly and Responsive - The first service increases customer satisfaction. (3) Procedure Factors: Fast and easy procedures in opening a BMT UGT sharia general savings account. The results of the study indicate that the combination of these three factors contributes significantly to increasing insight into BMT for the development of more effective strategies to maintain and sustain conservation.